Clinically relevant and simple immune system measure is related to symptom burden in bipolar disorder. Issue 5 (7th December 2017) - Köhler-Forsberg, Ole; Sylvia, Louisa; Deckersbach, Thilo; Ostacher, Michael Joshua; McInnis, Melvin; Iosifescu, Dan; Bowden, Charles; McElroy, Susan; Calabrese, Joseph; Thase, Michael; Shelton, Richard Charles; Tohen, Mauricio; et al.
Abstract : Objective: Immunological theories, particularly the sickness syndrome theory, may explain psychopathology in mood disorders. However, no clinical trials have investigated the association between overall immune system markers with a wide range of specific symptoms including potential gender differences. Methods: We included two similar clinical trials, the lithium treatment moderate-dose use study and clinical and health outcomes initiatives in comparative effectiveness for bipolar disorder study, enrolling 765 participants with bipolar disorder. At study entry, white blood cell (WBC) count was measured and psychopathology assessed with the Montgomery and Aasberg depression rating scale (MADRS). We performed analysis of variance and linear regression analyses to investigate the relationship between the deviation from the median WBC, and multinomial regression analysis between different WBC levels. All analyses were performed gender-specific and adjusted for age, body mass index, smoking, race, and somatic diseases. Results: The overall MADRS score increased significantly for each 1.0×10 9 /l deviation from the median WBC among 322 men (coefficient=1.10; 95% CI=0.32–1.89; p =0.006), but not among 443 women (coefficient=0.56; 95% CI=−0.19–1.31; p =0.14). Among men, WBC deviations were associated with increased severity of sadness, inner tension, reduced sleep, reduced appetite, concentration difficulties, inability to feel, and suicidal thoughts. Among women, WBC deviations were associated with increased severity of reduced appetite, concentration difficulties, lassitude, inability to feel, and pessimistic thoughts. Both higher and lower WBC levels were associated with increased severity of several specific symptoms. Conclusion: Immune system alterations were associated with increased severity of specific mood symptoms, particularly among men. Our results support the sickness syndrome theory, but furthermore emphasise the relevance to study immune suppression in bipolar disorder. Due to the explorative nature and cross-sectional design, future studies need to confirm these findings.